Residents´ perceptions of tourism development in Benalmádena (Spain) - Almeida-García, Fernando; Peláez-Fernández, María Ángeles; Cortés-Macías, Rafael; Balbuena-Vázquez, Antonia (My University, 2015)
This study examines the residents´ perceptions of the impact of tourism in Benalmádena, and the profiles of the residents according to socio-demographic characteristics. A questionnaire assessed how these characteristics influence the residents' perceptions towards the environment, economy, and socio-cultural aspects. The survey was administered to a stratified sample of 770 residents in Benalmádena. Results show a significant effect of socio-demographic variables on perception of tourism impact. The educational background, place of birth and how long respondents had been living in the community explain a significant amount of the variance in overall attitudes. Interaction analyses revealed that place of birth moderated the relationship between the tourism dimensions and the years of residence. For instance, the respondents with less than five years of residence showed more positive attitude towards the impact of tourism. We offer a profile of these residents according to their perceptions of the impact of tourism in their community.
DOI: 10.1016/j.tourman.2015.11.007
Keywords: Turismo - Benalmádena (Málaga); Residents; Tourism impacts; Resident attitudes; Costa del Sol; Benalmádena